Information and communication technologies as tools in environmental education (Biocenosis, 2021)
Abstract: Throughout history, human beings have looked for ways to satisfy their needs through learning. Hence, the last two decades have been characterized by the emergence, evolution, and revolution of technology, which has given way to a period of development, invention, and reinvention of various aspects regarding communication and learning within the society.  What we now know as the Fifth Technological Revolution started in the mid-twentieth century. Such revolution is based on the use of new information and telecommunications technology related to access to information and people´s communication skills, which has contributed to substantial changes regarding the population’s links to the socio-economic, cultural, political, and environmental reality. The evolutionary process of technological tools and methods has become both a challenge and an opportunity for education, especially for environmental education, in the process of sharing knowledge and information anywhere, breaking the spatial barriers produced by distance. The objective of this article is to know about the use and functionality of a series of technological tools that allow the strengthening and adjustment of the processes involved in environmental education.